2020
DOI: 10.15625/2615-9023/v42n4.14978
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions for squalene production and squalene extraction method of <i>Thraustochytrium<\i> sp. TN22

Abstract: Squalene, a natural triterpene with important roles as antioxidant, skin hydrating, cardio-protection and detoxifier, has attracted the attention of researchers in the world. This study investigated the optimal culture conditions for squalene production and to develop a method for squalene extraction and purification from cell suspension of Thraustochytrium sp. TN22. The results showed that squalene production by the strain Thraustochytrium sp. TN22 was optimum at 2% glucose, 0.5% yeast extract and 0,14% mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…TN22 can reach 95.30 mg/L. 66,67 Moreover, the C/N ratio also has an important effect on the squalene production. Various C/N ratios including 10:1, 20:1, 40:1, 60:1 and 80:1 were studied to investigate their effects on squalene production.…”
Section: External Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…TN22 can reach 95.30 mg/L. 66,67 Moreover, the C/N ratio also has an important effect on the squalene production. Various C/N ratios including 10:1, 20:1, 40:1, 60:1 and 80:1 were studied to investigate their effects on squalene production.…”
Section: External Substancesmentioning
confidence: 99%
“…It was found that when YPD medium was supplemented with 0.14% vitamin (B1, B6, and B12), the squalene titer by using Throstochytrium sp. TN22 can reach 95.30 mg/L. , Moreover, the C/N ratio also has an important effect on the squalene production. Various C/N ratios including 10:1, 20:1, 40:1, 60:1 and 80:1 were studied to investigate their effects on squalene production.…”
Section: Optimization Of Fermentation Conditionsmentioning
confidence: 99%